Bioedaphic stimulation and physiological response in Cicer arietinum bioaugmented with nutrient-solubilizing and pesticide-degrading Burkholderia species - Satya, Shalni; Dashora, Milap; Dar, Mohd Ashraf; Palsania, Preksha; Kaushik, Garima (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2026)
The escalating population has intensified the demand for sustainable agricultural practices that address nutrient deficiencies and pesticide pollution in soil. This study explores the dual potential of soil bacteria in nutrient solubilization and pesticide degradation, addressing two major challenges by three strains (SG1, SG5, and SG6), identified as Burkholderia spp. Qualitative and quantitative analysis revealed that strains had high solubilization efficiency for phosphate (PO43--P) (530 %- 1053.75 mg.L-1), potassium (K+) (367 %- 11.5 mg.L-1), and zinc (Zn) (490 %- 838.04 mg.L-1), validated by reduced pH and an increased electrical conductivity (EC). B. cenocepacia demonstrated maximum pesticide degradation (quinalphos), showing the highest degradation rates for both analytical (40.56 %) and commercial grade (74.05 %) of pesticide. Pot experiments with Cicer arietinum L. confirmed these findings while inoculating with Burkholderia spp., which significantly improved soil properties like increasing soil organic matter (up to 11.06 %), total organic carbon (6.41 %), and nutrient levels, including PO43--P, K+ (146.5 mg kg-1), and Zn (775.6 mg kg-1). Correlation analysis showed significant association in leaf area and pigment levels, while stem proliferation traded off against it. Principal Component Analysis (PCA) revealed that different treatments uniquely enhanced plant performance. B. lata increased biomass and stress tolerance, B. cenocepacia improved root physiology and nutrient uptake, while B. orbicola promoted morphological development. Hence, Burkholderia spp. can be promoted as effective bioinoculants for enhancing nutrient availability and bioremediation of pesticide-contaminated soils, while enhancing plant growth, offering a promising strategy for sustainable agriculture and improved soil health, leading towards Sustainable Development Goals (SDG) 12.
Keywords: Bioinoculant; Biodegradation; Bacteria; Solubilization; Quinalphos; SINGLE-SOLUTION METHOD; CHICKPEA GROWTH; SOIL; PHOSPHATE; ZINC; TOXICITY; YIELD; Plant Sciences